Literature review of microgrids - Fossati, Juan Pablo (2011)
The purpose of this article is to give an overview of the technologies that are being developed in the field of electricity networks. Future electricity networks must provide all consumers with a reliable, flexible, accessible and cost-effective power supply. In this respect smart grids are one of the most promising alternatives to face the energetic challenges. This article is indented to explain how information technologies, renewable energies, and storage energy devices are integrated in order to constitute the electricity network of the future.